Associations of plasma von Willebrand Factor levels with cognitive decline and neurodegeneration in older adults without dementia - Fu, Pan; Hu, Meiling (Frontiers in Aging Neuroscience, 2025)
BackgroundPrevious studies have suggested that von Willebrand Factor (VWF) may be implicated in the pathogenesis of Alzheimer’s disease (AD). However, the association between plasma VWF levels and cognitive decline and neurodegeneration in older adults without dementia remains unclear.MethodsWe investigated the cross-sectional and longitudinal associations between plasma von Willebrand Factor (VWF) levels and cognitive decline, as measured by the Mini-Mental State Examination (MMSE) and the Clinical Dementia Rating Scale Sum of Boxes (CDR-SB), as well as the volumes of six brain regions: the hippocampus, entorhinal cortex, middle temporal gyrus, fusiform gyrus, ventricles, and whole brain. Linear mixed-effects models were used to assess the association between plasma VWF levels and longitudinal changes in cognitive function and neuroimaging markers over time.ResultsThe study cohort consisted of 340 older adults without dementia at baseline. We observed that lower plasma VWF levels were associated with a faster rate of cognitive decline (MMSE: coefficient = 0.204, 95% CIs = [0.030, 0.378], p-value = 0.021; CDR-SB: coefficient = −0.268, 95% CIs = [−0.374, −0.163], p-value <0.001). Additionally, lower plasma VWF levels were linked to a more rapid reduction in the volumes of the hippocampus (coefficient = 0.016, 95% CIs = [0.004, 0.027], p-value = 0.009), entorhinal cortex (coefficient = 0.031, 95% CIs = [0.014, 0.048], p-value <0.001), and fusiform gyrus (coefficient = 0.047, 95% CIs = [0.008, 0.085], p-value = 0.017), as well as a faster enlargement of the ventricles (coefficient = −0.380, 95% CIs = [−0.558, −0.203], p-value <0.001). However, no significant relationships were observed between plasma VWF levels and changes in the volumes of the middle temporal gyrus or the whole brain (all p-values > 0.05).ConclusionOur findings may contribute to the growing body of knowledge on the vascular contributions to cognitive function and may help identify potential biomarkers for the early detection and intervention of AD.